Ulcerative interstitial cystitis in an adolescent successfully treated with complete transurethral ulcer resection: A case report. Issue 1 (14th December 2018) - Yuki, Eri; Obara, Kenji; Kuroki, Hiroo; Yamazaki, Hiroyuki; Yamana, Kazutoshi; Tadokoro, Akira; Hiruma, Kaede; Tomita, Yoshihiko
Abstract : Introduction: Interstitial cystitis is difficult to treat and may affect adolescents. Case presentation: A 15‐year‐old girl presented with severe pain upon terminal micturition that persisted for approximately 2 hours. The pain had been present for more than 1 month. Cystoscopy revealed severe erosion throughout the trigone. Transurethral fulguration did not improve her symptoms. However, complete electric resection of the ulcer markedly reduced the symptom. After complete resection, pain on urination disappeared and she has had no pain without medication for 15 months. Conclusion: Complete resection not fulguration of the ulcer is effective for interstitial cystitis in adolescent female patients.